Ovarian hyperstimulation syndrome leading to ventriculoperitoneal shunt malfunction: Case report. (June 2018) - Azriel, Amit; Fleming, Benjamin; Dior, Uri P.; Moscovici, Samuel; Sufaro, Yuval; Awad, Mohammed; Drummond, Kate
Highlights: Ventriculoperitoneal shunt (VPS) insertion is a common neurosurgical procedure. VPS malfunction is not uncommon, and may arise from abdominal pathologies among others. Ovarian Hyperstimulation Syndrome (OHSS) may lead to ascites and subsequent VPS malfunction. Awareness of abdominal etiologies to VPS malfunction is crucial. Abstract: Ventriculoperitoneal shunt (VPS) insertion is a common neurosurgical procedure for hydrocephalus. Unfortunately, VPS malfunction is not uncommon, with an estimated cumulative rate of 32% at 5 years. As flow through the shunt is influenced by the pressure gradient between the ventricles and the peritoneal cavity, malfunction may be caused by elevated intra-abdominal pressure. We present a rare patient with ascites following ovarian hyperstimulation syndrome (OHSS) leading to shunt malfunction. OHSS is a potentially life-threatening complication of controlled ovarian stimulation caused by the administration of exogenous gonadotropins. In this patient clinical and radiological resolution of shunt dysfunction were achieved following peritoneocentesis. To our knowledge this is the first described case of OHSS leading to shunt malfunction, emphasizing the importance of awareness, early recognition and proper management of abdominal etiologies of VPS malfunction.